From Research to Practice in OBGYN: How to Critically Interpret Studies in Implementation. Issue 2 (31st March 2022) - Hamm, Rebecca F.; Moniz, Michelle H.
Abstract : There is a growing body of research that addresses implementation-focused questions within obstetrics and gynecology. With this document, we provide clinicians with the necessary tools to critically read and interpret literature evaluating an implementation endeavor. We describe the process of implementation research, as well as common study designs and outcomes. Furthermore, we detail pitfalls in the design and analysis of implementation studies, using examples within obstetrics and gynecology. Armed with this knowledge, clinicians may better be able to translate a paper on implementation into improvement efforts in their own clinical practice setting.